The chemical and genetic basis of tomato flavour - Jasionowicz, Piotr (2012)
Tomatoes often lack the characteristic good taste that consumers expect. In recent years, the fruit and vegetable industry has focused on traits such as yield, colour, and fruit size; however, flavour has been largely forgotten, at least for varieties that are grown in bulk and are cheap to purchase. Tomato volatiles are one of the most important flavour contributors along with sugars and organic acids. Over 400 volatiles are present in tomato, but only about 30 are considered critical to tomato flavour. The purpose of this study was to identify volatile Quantitative Trait Loci (vQTL) using publicly available Solanum pennellii and Solanum habrochaites introgression lines (ILs). Detection of vQTL is an essential milestone for identification of candidate genes involved in tomato flavour. Identification of vQTL was undertaken by screening the ILs using Atmospheric Pressure Chemical Ionisation Mass Spectrometry (APCI-MS) and Gas Chromatography Mass Spectrometry (GC-MS). Additionally key volatiles and their interactions were evaluated in a series of sensory experiments using tomato juice and tomato purée. The study revealed that, the S. pennellii population had several major effects including those on IL1-4, which had a vQTL for C6 volatile E-2-hexenal. It was possible to identify a sub-IL, 1-4-1 that also harboured this vQTL. In this IL1-4-1 region of chromosome 1, 122 genes were present including a possible, candidate gene likely to be involved in lipoxygenase pathway. The sensory experiments showed strong impact of methyl salicylate on other volatiles; E-2-hexenal and citral showed positive effects in purée studies. Determined taste detection thresholds for volatiles in tomato juice and purée were established. Keywords: volatile, genes, tomato juice, tomato purée, flavour